A study of hybrid clarification-filtration processes for potable water treatment - Price, Robert (2005)
This research investigates the removal of natural organic matter (NOM) from low turbidity waters by optimising an integrated coagulation and membrane filtration process. In conjunction with a regional water utility, the feasibility and operability of pre-coagulation with ultrafiltration membrane units, is investigated at both the fundamental and applied levels.